EFFECT OF VARIOUS LEVELS OF DIGESTIBLE ENERGY AND PROTEIN IN THE DIET ON THE GROWTH OF “GAMITANA” (COLOSSOMA MACROPOMUM) CUVIER 1818 - Gutiérrez A., Félix Walter (2009)
A factorial experiment was conducted to evaluate the effect of diets with two levels of protein (25 and 35%) and three levels of digestible energy (2.3, 2.5, and 2.7 kcal/g) on the “gamitana” Colossoma macropomum in terms of body weight gain (WG), food conversion (FC), retained energy (RE), and protein efficiency ratio (PER). Diets contained anchovy and soybean meal as protein sources, and yellow corn, wheat bran, and brewery bran as energy sources. There were highly significant interactions (p<0.01) between protein concentration and digestible energy on the “gamitana” growth. In diets with 25% protein, the increase of digestible energy significantly enhanced WG, FC, RE, and PER, where the level of 2.7 kcal/g had the best performance. However, in diets with 35% protein, only the 2.7 kcal/g level showed good results. It can be concluded that the best response was obtained with a diet containing 2.7 kcal of energy digestible/g and 25% protein.